Peran Artificial Intelligence Marketing dan Content Marketing dalam Meningkatkan Purchase Intention Produk melalui Brand Trust - Khoirunnisa Diah Parwitasari; Dandy Kurnia (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to analyze the influence of Artificial Intelligence Marketing and Content Marketing on Purchase Intention of local skincare products among TikTok Shop users, with Brand Trust serving as an intervening variable. The study is motivated by the increasing utilization of artificial intelligence technology and content-based marketing strategies in enhancing consumers' purchase intentions within social commerce platforms. A quantitative approach with a survey method was employed in this study. Data were collected through questionnaires distributed to 100 respondents who were TikTok Shop users and had searched for or purchased local skincare products. The sampling technique used was purposive sampling, while data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Artificial Intelligence Marketing and Content Marketing have a positive and significant effect on Brand Trust. Furthermore, Artificial Intelligence Marketing, Content Marketing, and Brand Trust were found to have positive and significant effects on Purchase Intention. The indirect effect analysis revealed that Brand Trust significantly mediates the relationship between Artificial Intelligence Marketing and Content Marketing and Purchase Intention. These findings suggest that optimizing artificial intelligence in marketing activities and delivering high-quality content can enhance consumers' trust in brands, thereby increasing their intention to purchase local skincare products through TikTok Shop.